Myocardial depression in sepsis: From pathogenesis to clinical manifestations and treatment - Antonucci, Elio; Fiaccadori, Enrico; Donadello, Katia; Taccone, Fabio Silvio; Franchi, Federico; Scolletta, Sabino (Journal of critical care, 2014)
The cardiovascular system plays a key role in sepsis, and septic myocardial depression is a common finding associated with increased morbidity and mortality. Myocardial depression during sepsis is not clearly defined, but it can perhaps be best described as a global (systolic and diastolic) dysfunction of both the left and right sides of the heart. The pathogenesis of septic myocardial depression involves a complex mix of systemic (hemodynamic) factors and genetic, molecular, metabolic, and structural alterations. Pulmonary artery catheterization and modern echo-Doppler techniques are important diagnostic tools in this setting. There are no specific therapies for septic myocardial depression, and the cornerstone of management is control of the underlying infectious process (adequate antibiotic therapy, removal of the source) and hemodynamic stabilization (fluids, vasopressor and inotropic agents). In this review, we will summarize the pathogenesis, diagnosis, and treatment of myocardial depression in sepsis. Additional studies are needed in order to improve diagnosis and identify therapeutic targets in septic myocardial dysfunction.